Optimizing Sustainable Wastewater Treatment: Kinetic and Parametric Study of Methylene Blue Removal Using Electrocoagulation - Amir Husin; Dermala Tito A; Fadhila Fadhila; Lies Setyowati; Deny Supriharti (Jurnal Penelitian Pendidikan IPA, 2026)
This study investigates the removal of Methylene Blue (MB) from synthetic wastewater using a batch electrocoagulation (EC) reactor with two pairs of parallel monopolar iron electrodes, directly supporting Sustainable Development Goal 6 (Clean Water and Sanitation). Operational parameters, including initial pH, inter-electrode distance, applied voltage, and electrolysis time, were systematically evaluated. Within 15 minutes of electrolysis, a color removal efficiency of over 80% was achieved at an applied voltage of 10 V and an inter-electrode distance of 5 mm. Treatment efficiency decreased to 60.13% when the inter-electrode distance was widened to 10 mm due to increased cell resistance. Conversely, increasing the voltage from 10 V to 20 V and 30 V significantly enhanced the process efficiency. The MB removal rate was validated using a mass transfer-based kinetic model solved via the 4th-order Runge-Kutta method. The model aligned well with experimental data, displaying a Sum of Squared Errors (SSE) range of 0.09 to 193.57. At an extended electrolysis time of 75 minutes, the average efficiency reached 92.04% across all voltage variations, proving that coagulant saturation overcomes mass transfer limitations.